PERAN IBU DALAM MENDORONG ANAK PEREMPUAN MEREKA UNTUK MELANJUTKAN PENDIDIKAN KE JENJANG LEBIH TINGGI - Safitri, Della; Lestari, Dian; Arimbi, Dwi; Sari, Fira Duwi Novita; Annisa, Maya; Rambe, Mirza Syadat (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This article discusses the role of mothers in encouraging girls to continue their education to a higher level: Education is an important factor in improving the quality of life and future of girls. However, there are still various obstacles that prevent girls from continuing their education to a higher level, both economic and family environment factors. This article aims to discuss the role of mothers in encouraging girls' awareness of education to a higher level. The method used in writing this article is a literature study by reviewing various sources such as books, journals, and scientific articles that are relevant to the scientific topic. The results of the discussion show that mothers play an important role in encouraging girls' awareness of education through several forms of involvement, including providing motivation, managing household finances for the sake of continuing education, and providing guidance in making decisions about girls' education. Mothers' support in the form of attention, advice, and moral encouragement can increase girls' enthusiasm for learning and their confidence to continue their education. Thus, mothers play a very influential role in determining the success of girls' education to a higher level. ABSTRAK Artikel ini membahas peran ibu dalam mendorong anak perempuan untuk melanjutkan pendidikan ke jenjang lebih tinggi : Pendidikan merupakan faktor penting dalam meningkatkan kualitas hidup dan masa depan anak perempuan. Namun, masih terdapat berbagai kendala yang menyebabkan anak perempuan tidak melanjutkan pendidikan ke jenjang yang lebih tinggi, baik dari faktor ekonomi, maupun lingkungan keluarga . Artikel ini bertujuan untuk membahas peran ibu dalam mendorong kesadaran pendidikan anak perempuan ke jenjang yang lebih tinggi. Metode yang digunakan dalam penulisan artikel ini studi literatur dengan mengkaji berbagai sumber seperti buku, jurnal, dan artikel ilmiah yang relevan dengan topik ilmiah. Hasil pembahasan menunjukan bahwa ibu berperan penting dalam mendorong kesadaran pendidikan anak perempuan melalui beberapa bentuk keterlibatan , antara lain memberi motivasi, mengelola keuangan rumah tangga demi keberlangsungan pendidikan serta pengarah dalam pengambilan keputusan pendidikan anak perempuan. Dukungan ibu yang berupa perhatian, nasihat, dan dorongan moral mampu meningkatkan semangat belajar serta kepercayaan diri anak perempuan untuk melanjutkan pendidikan. Dengan demikian, peran ibu sangat berpengaruh dalam menentukan keberhasilan pendidikan anak perempuan hingga kejenjang yang lebih